Left vs. right radial approach for coronary catheterization: Relation to age and severe aortic stenosis - Will, Maximilian; Weiss, Thomas W.; Weber, Michael; Kwok, Chun Shing; Borovac, Josip A.; Lamm, Gudrun; Unterdechler, Markus; Aufhauser, Simone; Nolan, Jim; Mascherbauer, Julia; Schwarz, Konstantin (Frontiers in Cardiovascular Medicine, 2022)
Background: Old age and the presence of aortic stenosis are associated with unfolding of the intrathoracic aorta. This may result in increased difficulties navigating catheters from right compared to left radial approach. Objective: To investigate whether increasing age or presence of severe aortic stenosis were associated with increased catheterization success rates from left (LRA) compared to right radial artery approach (RRA). Methods: We compared coronary angiography success rates of RRA and LRA according to different age groups and in a subgroup of patients with severe aortic stenosis. Results: A total of 21259 coronary angiographies were evaluated. With increasing age, the first pass success rate from either radial access decreased significantly (p<0.001). In patients <85 years of age there was no difference between LRA and RRA. However, in patients ≥85 years of age, LRA was associated with significantly higher success rates compared to RRA (90.1% vs 82.8%, p=0.003). Patients ≥85 years of age received less contrast agent and had shorter fluoroscopy time when LRA was used (86.6±41.1 ml vs. 99.6±48.7 ml (p<0.001) and 4.5±4.1 min vs. 6.2±5.7 min (p<0.001), mean (±SD)). In patients with severe aortic stenosis (n=589) better first pass success rates were observed via LRA compared to RRA route (91.9%, vs 85.1% vs. p=0.037). Conclusion: LRA, compared to RRA is associated with higher first pass catheter success rate for coronary artery angiography in patients ≥ 85 years of age and those with severe aortic stenosis.